2022
DOI: 10.1136/bmjopen-2022-061352
|View full text |Cite
|
Sign up to set email alerts
|

Towards consensus: defining and supporting a professional role for pharmacists associated with traditional and complementary medicines – a protocol of implementing an international e-survey

Abstract: IntroductionTraditional and complementary medicines (T&CM) are predominantly self-selected from retail outlets including pharmacies as part of self-care practices. Concerns about the appropriate and safe use of T&CM products raises questions about ‘should’ and ‘how’ pharmacists could adopt professional responsibilities. There lacks a consensus about the scope of these responsibilities, or the initiatives required to execute them. The aim of this study is to identify an international set of core respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A cross-sectional online survey with convenience sampling was conducted across nine countries: Carbo Verde, China, Croatia, Lebanon, Malaysia, Philippines, Portugal, Saudi Arabia, and Thailand. The full study protocol is reported elsewhere ( Harnett et al, 2022 ) in accordance with the guidelines of STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) ( Von Elm et al, 2007 ) and the Checklist for Reporting Results of Internet E-Surveys (CHERRIES) ( Eysenbach, 2004 ). This cross-country collaboration was led by researchers based at the Institute of Chinese Medical Sciences, University of Macau, and The University of Sydney School of Pharmacy, Faculty of Medicine and Health in New South Wales, Australia.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A cross-sectional online survey with convenience sampling was conducted across nine countries: Carbo Verde, China, Croatia, Lebanon, Malaysia, Philippines, Portugal, Saudi Arabia, and Thailand. The full study protocol is reported elsewhere ( Harnett et al, 2022 ) in accordance with the guidelines of STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) ( Von Elm et al, 2007 ) and the Checklist for Reporting Results of Internet E-Surveys (CHERRIES) ( Eysenbach, 2004 ). This cross-country collaboration was led by researchers based at the Institute of Chinese Medical Sciences, University of Macau, and The University of Sydney School of Pharmacy, Faculty of Medicine and Health in New South Wales, Australia.…”
Section: Methodsmentioning
confidence: 99%
“…The survey was constructed using the online survey platform Survey Monkey. The processes for developing and testing the survey are outlined in the study protocol ( Harnett et al, 2022 ). When translation from English to another language was required for dissemination in non-English speaking countries, the collaborator located in that country organized the translation of the survey instrument and further testing for face validity.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations